A randomized, double‐blind, phase II study of oral histone deacetylase inhibitor resminostat plus S‐1 versus placebo plus S‐1 in biliary tract cancers previously treated with gemcitabine plus platinum‐based chemotherapy. (26th February 2021) - Ueno, Makoto; Morizane, Chigusa; Furukawa, Masayuki; Sakai, Daisuke; Komatsu, Yoshito; Nakai, Yousuke; Tsuda, Masahiro; Ozaka, Masato; Mizuno, Nobumasa; Muto, Manabu; Fukutomi, Akira; Ikeda, Masafumi; et al.
Abstract: Purpose: Effective second‐line chemotherapy options are limited in treating advanced biliary tract cancers (BTCs). Resminostat is an oral histone deacetylase inhibitor. Such inhibitors increase sensitivity to fluorouracil, the active form of S‐1. In the phase I study, addition of resminostat to S‐1 was suggested to have promising efficacy for pre‐treated BTCs. This study investigated the efficacy and safety of resminostat plus S‐1 in second‐line therapy for BTCs. Methods: Patients were randomly assigned to receive resminostat or placebo (200 mg orally per day; days 1–5 and 8–12) and S‐1 group (80–120 mg orally per day by body surface area; days 1–14) over a 21‐day cycle. The primary endpoint was progression‐free survival (PFS). Secondary endpoints comprised overall survival (OS), response rate (RR), disease control rate (DCR), and safety. Results: Among 101 patients enrolled, 50 received resminostat+S‐1 and 51 received placebo+S‐1. Median PFS was 2.9 months for resminostat+S‐1 vs. 3.0 months for placebo+S‐1 (HR: 1.154, 95% CI: 0.759–1.757, p  = 0.502); median OS was 7.8 months vs. 7.5 months, respectively (HR: 1.049, 95% CI: 0.653–1.684, p  = 0.834); the RR and DCR were 6.0% vs. 9.8% and 70.0% vs. 78.4%, respectively. Treatment‐related adverse events (TrAEs) of grade ≥ 3 occurring more frequently (≥10% difference) in the resminostat+S‐1 than in the placebo+S‐1 comprised platelet count decreased (18.0% vs. 2.0%) and decreased appetite (16.0% vs. 2.0%). Conclusions: Resminostat plus S‐1 therapy improved neither PFS nor OS for patients with pre‐treated BTCs. Addition of resminostat to S‐1 was associated with higher incidence of TrAEs, but these were manageable (JapicCTI‐183883). Abstract : This randomized, placebo‐controlled, double‐blind study investigated the efficacy and safety of resminostat plus S‐1 as a second‐line therapy in patients with BTCs. This was the first randomized study to use S‐1, which is widely used in second‐line treatment for BTC patients in Japan, as an active comparator. The results showed that resminostat plus S‐1 prolonged neither PFS nor OS in comparison with placebo plus S‐1.